9t+3=6t+15

Simple and best practice solution for 9t+3=6t+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9t+3=6t+15 equation:



9t+3=6t+15
We move all terms to the left:
9t+3-(6t+15)=0
We get rid of parentheses
9t-6t-15+3=0
We add all the numbers together, and all the variables
3t-12=0
We move all terms containing t to the left, all other terms to the right
3t=12
t=12/3
t=4

See similar equations:

| x(-7)=63 | | 2(1+b)=-7+5b | | 5-3x-3=25 | | 8-1.8=1.2x | | -3-7(2+4x)=95 | | 3(l+6)=39 | | (2x+3)=(4x+20) | | 2g-g+4=17 | | 28*9=18+-2x | | 64=4f | | 4-2n=16. | | -20=-4(5c+6) | | 3-7x-4=20 | | 1.5r+15.5=26 | | -56+7y+56=0 | | 5a=(-3)+.6a | | 2(n+8)=5n-8 | | -45=m+1.9 | | 2-3/2n=-82/5 | | -x=2x+8 | | (3y+2)(y+9)=0 | | x+11=9x+35 | | 5a=(-3)+(3/5a) | | -34+3r=5(8+8r) | | X2-16x=10 | | d/8-2=1 | | –2.8(x+4.9)=18.2 | | 6.5(x–4)=19.5 | | -5a=-3+3/5a | | 5x-1=3x*7 | | 6x+33=135 | | X2-24x=10 |

Equations solver categories